Removal behavior of slime from pentlandite surfaces and its effect on flotation. (15th August 2018) - Feng, Bo; Peng, Jinxiu; Zhang, Wenpu; Luo, Guodong; Wang, Huihui
Graphical abstract: Highlights: Slimes were attached to coarse particle surfaces. HIC method can be used to remove coarser slime. SHMP can be used to remove fine slime. The HIC and SHMP should use together. Abstract: Jinchuan is the largest nickel producer in China. The separation of pentlandite from serpentine gangue is difficult in this flowsheet because serpentine slime can attach to the valuable minerals as a slime coating. To solve this problem, the removal of different sized serpentine slimes from sulfide surfaces and its effect on flotation were studied using flotation experiments, particle size analysis, and X-ray diffraction. The results illustrated that the slime particles attached to coarse particle surfaces after grinding and depressed pentlandite flotation. The slimes comprised mainly MgO minerals. High-intensity conditioning could be used to remove the coarser slimes, while sodium hexametaphosphate could be used to remove the fine slimes. These two methods were used in combination in the flotation of Jinchuan nickel sulfide ore and the metallurgical performance was significantly improved: nickel recovery increased from 82.97% to 86.27% and the MgO content decreased to 6.22%.